Rancang Bangun Aplikasi Monitoring Prestasi dan Tata Tertib Mahasiswa Menggunakan Framework Laravel Berbasis Website di Polimarin - Santoso, Gunawan Budi; Juwarlan, J; Anwar, Amthori; Widodo, W; Saputra, Agung; Alfiana, Akhmad Busyroh; Setiawan, Bagus; Lestari, Ayu (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2026)
The student performance and discipline monitoring application is a system designed to assist in the digital management of academic and behavioral data of students. This study aims to develop a web-based application using the Laravel framework to meet the needs of the Polimarin. The application is designed to monitor student performance progress and efficiently document disciplinary violations. The system development method uses the Waterfall model, which includes the stages of analysis, design, testing,implementation, and evaluation. The Laravel framework was chosen due to its advantages in data management, security, and ease of integration. Other supporting technologies include MySQL for the database, as well as HTML, CSS, and JavaScript for user interface development. This study resulted in a web-based monitoring application with several main features, such as academic performance data management, disciplinary violation recording, and report generation in the form of graphs and tables. System testing shows that the application functions according to user needs and is capable of improving efficiency in student data management.